Integrasi Nilai-nilai Kearifan Lokal dalam Manajemen Pendidikan Pesantren: Studi pada Dayah Raudhatul Ma’arif Al-Aziziyah Cot Trueng - Zulfikar, Zulfikar; Daud, Al Husaini M; Salabi, Agus Salim (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2024)
This study focuses on local wisdom-based educational management at Dayah Raudhatul Ma’arif Al-Aziziyah Cot Trueng, one of the traditional Islamic educational institutions in Aceh. The background of this research is based on the importance of preserving and integrating local values into the pesantren education system to shape the character and leadership of students. The research employs a qualitative approach with data collection techniques including observation, in-depth interviews, and document analysis. The findings indicate that the implementation of educational management at this dayah successfully integrates local values, namely